Regional growth dynamics in India in the post- economic reform period - Mishra , Biswa Swarup (New York, 2007)
With economic reforms underway for more than a decade in India, it is interesting to explore the responses of the various states in the federal structure to the newer challenges. This book addresses a wide range of issues, such as growth dynamics, income inequality, the fiscal behaviour of the states, the role of the banking sector in the development process, the emerging institutional structure aimed at catering to social banking, and strategies for agricultural growth. The book provides a blend of analytical rigour and empirical sophistication. The comparative performance of the states has been analysed, and the insights into the reasons for spatial differences and the corrective measures needed offer ways of making the most of the opportunities unleashed in the reform process. The book provides ample application of diverse econometric techniques to contemporary economic issues.
Keywords: India-Economic policy-1991